Autologous Fat Transfer for Esthetic Contouring of Face in Posttraumatic Nonfunctional Maxillofacial Deformities. Issue 2 (June 2016) - Agrawal, Kapil S.; Bachhav, Manoj; Naik, Charudatta S.; Tanwar, Harshwardhan; Sankhe, Shilpa S.
The transfer of autologous fat has been performed since the 1890s; however, its popularity has increased owing to better understanding of fat harvesting and processing techniques. In this article, fat grafting procedure has been used to correct posttraumatic facial deformities in 25 cases. As healing of grafted fat is unpredictable, we have used longer follow-up of 2 years. Evaluation was performed using facial photographs and MRI scans. Scientific literature describes an absorption rate ranging from 20 to 90%. High fat graft resorption rates have been attributed to traumatic handling of the graft during harvest, processing, and injection. Various processing techniques have been suggested. The goal of these techniques is to obtain greater adipocyte cell survival and, consequently, more reliable clinical results. In our study, we have used syringe aspiration and low-speed centrifuge for processing of fat which has resulted in good clinical outcomes.